THE DYNAMICS OF HOUSE PRICE VOLATILITY IN MALAYSIA - Reen, Tan Ai; Razali, Muhammad Najib (Journal of Technology Management and Business, 2016)
The purpose of this study is to examine the house price volatility in three urban areas in Malaysia. This empirical study covers a sample period of 9 years from 2005 Q1 to 2013 Q4. The volatility of the Malaysian housing market and its determinants were investigated. The determinants for house price volatility were found through content analysis and ARCH model. An Autoregressive Conditional Heteroscedasticity (ARCH) model was employed in this study to examine the volatility of house prices of three Malaysian main urban areas. The Engle LM test was also utilized to analyze the volatility clustering effects in these provinces. This study found that there are evidence of volatility clustering in more than half of the housing in Malaysia. The significant determinants for the house price volatility in Malaysia are BLR, GDP, housing stock and inflation rate. This study has implications for policy and decision makers as they have to take into consideration house price volatility when drawing up policies and making investment decisions. Besides, the changes in house price volatility determinants will also affect the housing market. Therefore, the determinants are important in the formulation of housing policy. The limitations for this study are time constraint and the quality of the data. This paper is probably one of the few studies undertaken to examine house price volatility in Malaysia Keywords: House, price, volatility, Malaysia